2019
DOI: 10.1016/j.pmpp.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A method for generating virus-free cassava plants to combat viral disease epidemics in Africa

Abstract: Here, we report a method to clean cassava plants from viral infections that cause cassava mosaic and brown streak diseases in Africa. Infected plants of resistant or tolerant varieties from Malawi, Mozambique, Kenya, Tanzania and Uganda were cleaned in the UK using a combination of tissue culture, chemotherapy and thermotherapy. In the first cycle of our virus-indexing procedure, we successfully cleaned 27 of the 31 varieties (87%), and after an additional three cleaning cycles, all plants were virus-free. Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…During the current study, exposing the nodal explants to 20% Jik (3.85% NaOCl) for 15 min gave the highest (90%) clean explants. These results concur with those of Maruthi et al [28] who reported high percent (80-90%) clean explants when a commercial bleach (5% pure sodium hypochlorite) was used on some cassava cultivars. It also corroborates with the results of Waweru et al [29] who reported that the highest proportion (92%) of clean explants was obtained when the Cyphomandra betacea nodal explants were exposed to 15% Jik for 20 min.…”
Section: Discussionsupporting
confidence: 92%
“…During the current study, exposing the nodal explants to 20% Jik (3.85% NaOCl) for 15 min gave the highest (90%) clean explants. These results concur with those of Maruthi et al [28] who reported high percent (80-90%) clean explants when a commercial bleach (5% pure sodium hypochlorite) was used on some cassava cultivars. It also corroborates with the results of Waweru et al [29] who reported that the highest proportion (92%) of clean explants was obtained when the Cyphomandra betacea nodal explants were exposed to 15% Jik for 20 min.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison, the advanced methods consist of RNA silencing, cross-protection, transgenic plants, gene pyramiding, and protein-protein interaction [15]. In the latter, the virus can be eliminated in plant tissues (as opposed to simply avoiding or delaying the infection), though this process does interfere with the vectors, use of attenuated strains and resistant or tolerant varieties, and is very expensive [24][25][26]. Chemotherapy consists of the use of antivirals that treat some diseases in animals and is also useful for the treatment of viruses in plant tissue cultures [27].…”
Section: Current Options For Controlling Virus Diseases In Agriculturementioning
confidence: 99%
“…The clean and virus-free plant material used in this study originated from the 5CP project [14]. Plants were grown in a mixture of soil and compost (John Innes No.2; Fargo Ltd., Arundel, UK) in an insect-free quarantine glasshouse at 25 ± 5˚C, 50-60% relative humidity and L14:D10 (light:dark) hours for three months.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Since the raise and spread of African cassava whitefly superabundant populations, the development of improved cassava varieties possessing virus and whitefly resistance has constituted one of the core milestones of national breeding programs in Sub-Saharan African countries and international consortiums [8,11,12]. Efforts in finding natural sources of African whitefly (Bemisia tabaci) resistance have been focused on collections of local landraces and advanced lines originally developed for virus resistance [13][14][15][16][17] with the intention of pyramiding both disease and vector resistance into farmer-preferred varieties adapted to local agroecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation